WHO report on the global tobacco epidemic, 2013 : enforcing bans on tobacco advertising, promotion and sponsorship (World Health Organization, 2013)
The report examines in detail the two primary strategies to provide health warnings: labels on tobacco product packaging and anti-tobacco mass media campaigns. It provides a comprehensive overview of the evidence base for warning people about the harms of tobacco use as well as country-specific information on the status of these measures.